Photo-onycholysis Following Two Weeks of Doxycycline - KC, S; Karn, D; Shrestha, S (Journal of Nepal Health Research Council, 2016)
Photo-onycholysis is a form of phototoxic reaction characterized by spontaneous separation of the nail plate from the nail bed. It usually follows drug intake and tetracycline is a well-known culprit. We present a case of 19 years gentleman who developed this rare side effect following two weeks of ingestion of doxycycline. Keywords: Doxycycline; photo-onycholysis; tetracycline.